Interchain ordering structure and main chain conformation analysis of thermal stability in vinyl-addition polynorbornene. (4th October 2022) - Kai, Hideki; Izumi, Atsushi; Hayakawa, Shun; Niemiec, J. Alex; Ebner, Carl; Schofield, Mike; Skilskyj, Doug; Rhodes, Larry F.
Abstract: The aggregation structure and formation mechanism during film casting using toluene of vinyl-addition poly(norbornene- co -hexylnorbornene)s (P(NB/HNB)s) synthesized using Ni and Pd catalyst were systematically investigated by wide- and small-angle X-ray scattering and gel permeation chromatography–right-angle laser light scattering–viscometry techniques. The correlation of these data with the glass-transition temperature ( T g ) was discussed. The single-chain conformation of P(NB/HNB)s was a flexible, stretched structure with respect to the Gaussian chain in a good solvent, as characterized by an exponent of the Mark–Houwink–Sakurada equation, and P(NB/HNB)s formed thin-rod aggregates with a length of 30 nm in semi-concentrated toluene solution via interchain stacking of the rod-like chains. P(NB/HNB) films cast from toluene solution exhibit interchain ordering structures with distances between 0.9 and 1.7 nm depending on the NB/HNB ratio. These findings show that the interchain ordering is driven by the stacking of the rod-like chains, which resulted in the highly ordered interchain structure in the film. The T g of the Pd-catalyzed polymer films were 20 °C higher than that of the Ni-catalyzed polymer films depending on the interchain structure. There is a strong correlation between interchain ordering structure and T g, which shows that the T g of P(NB/HNB)s is primarily influenced by the van der Waals interaction between main chains. Graphical abstract: Image 1 Highlights: Aggregation structure and mechanism of vinyl-addition polynorbornenes was investigated. The polymers formed thin-rod aggregates in semi-concentrated solution and highly ordered interchain structure in the film. The interchain ordering was driven by the stacking of the rod-like chains during drying process. There is a strong correlation between T g of the film and the interchain ordering structure.